2023
DOI: 10.1039/d2ay02106d
|View full text |Cite
|
Sign up to set email alerts
|

Determination and quantification of related substances and degradation products in bictegravir by full factorial design evaluated HPLC and mass spectrometry

Abstract: Determining and quantifying novel Impurities and degraded impurities of a drug product is always a continuous challenge to enhancing the drug quality for patients' safety. Herein, our work deals with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In general, the technique should be enhanced or its robustness should be proven using the quality by design (QbD) approach, according to the present regulatory criteria, which are unambiguous. The robustness of the recently presented strategy was demonstrated using the QbD tool (Dandabattina et al, 2023; Jythesh Kumar et al, 2023; Konduru et al, 2022; Kowtharapu et al, 2022; Vemuri et al, 2022). The design of experiments based on QbD were carried out using Design‐Expert software version 13 (Stat‐Ease, Inc., Minneapolis, MN).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the technique should be enhanced or its robustness should be proven using the quality by design (QbD) approach, according to the present regulatory criteria, which are unambiguous. The robustness of the recently presented strategy was demonstrated using the QbD tool (Dandabattina et al, 2023; Jythesh Kumar et al, 2023; Konduru et al, 2022; Kowtharapu et al, 2022; Vemuri et al, 2022). The design of experiments based on QbD were carried out using Design‐Expert software version 13 (Stat‐Ease, Inc., Minneapolis, MN).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the sensitivity and toxicity of this impurity (its consumption of high levels will cause cancer), we have selected the RP-HPLC-MS/MS technique for the estimation of 2-amino-4-chlorophenol in ppm level (Figure 1) [19][20][21][22][23]. Both methods were developed and validated considering the International Council for Harmonization (ICH) requirements, which met its acceptance criteria and were found to be specific, linear, accurate, precise, and robust [24][25][26][27][28]. The results of the forced degradation study confirmed that the developed RP-HPLC-UV method is stabilityindicating, in addition to being specific and selective in the separation and quantitative determination of organicrelated impurities of chlorzoxazone drug substance and drug product [29,30].…”
Section: Introductionmentioning
confidence: 99%